Pengaruh Pemanfaatan Media Video Terhadap Hasil Belajar IPAS Kelas IV SD GMIM 1 Tombatu - Tandayu, Megita Prity; Rorimpandey, Widdy H.F.; Mongdong, Romi Junior (Peneliti.net, 2024)
The aim of the research is to determine the effect of using video media on science learning outcomes for class IV students at SD GMIM 1 Tombatu, with 20 students in class IVa and 20 students in class IVb. This research uses a quantitative research approach with experimental research methods, in the form of Quasi Experimental Design, nonequivalent control group design with prerequisite tests (normality test and homogeneity test) and hypothesis testing (independent sample t-test). From the results obtained, the experimental class got an average post-test score of 84.25, while the control class was 63.25, so from these data it can be stated that the two classes had differences in post-test learning outcomes. The Kolmogorov-Smirnov normality test in the experimental class pre-test .006, post-test .089 and in the control class pre-test .077 and post-test .052 was declared normal because the sig value was >0.05. And the homogeneity test of the experimental class and control class data is .103 which states >0.05 so it is said to be homogeneous. And the independent sample t-test probability sig (2-tailed) is .000, this is <0.05, so Ha is accepted and Ho is rejected. So it can be stated that there are significant differences between the two experimental and control class groups. Based on the results of research and discussions in class IV at SD GMIM 1 Tombatu, it can be concluded that the influence of the use of video media on class IV science and science learning outcomes regarding energy changes can influence learning outcomes